Relationships between dysphagia and tongue pressure during swallowing in Parkinson's disease patients. (6th April 2018) - Minagi, Y.; Ono, T.; Hori, K.; Fujiwara, S.; Tokuda, Y.; Murakami, K.; Maeda, Y.; Sakoda, S.; Yokoe, M.; Mihara, M.; Mochizuki, H.
Summary: Although dysphagia is a life‐threatening problem in patients with Parkinson's disease (PD), the pathophysiology of oropharyngeal dysphagia is yet to be understood. This study investigated the tongue motor function during swallowing in relation to dysphagia and the severity of PD. Thirty patients with PD (14 males and 16 females; average age, 69.4 years), Hoehn and Yahr stage II‐IV, in Osaka University Hospital are participated in this study. During swallowing 5 ml of water, tongue pressure on the hard palate was measured using a sensor sheet with 5 measuring points. The maximal tongue pressure at each measuring point during swallowing was compared between patients with PD and healthy controls. Subjective assessment of oropharyngeal dysphagia was performed using Swallowing Disturbance Questionnaire‐Japanese. The maximal tongue pressure at each measuring point was significantly lower in patients with PD than in healthy controls (8 males and 12 females; average age, 71.6 years). Furthermore, the maximal tongue pressure was significantly lower in dysphagic PD patients than non‐dysphagic PD patients. Loss of tongue pressure production at the anterior part of the hard palate was strongly related to dysphagia in the oral phase as well as in the pharyngeal phase. An abnormal pattern of tongue pressure production was more frequently observed in dysphagic PD patients than in non‐dysphagic PD patients. The results suggest that tongue pressure measurement might be useful for early and quantitative detection of tongue motor disability during swallowing in patients with PD.